Pattern-reconfigurable water horn antenna - Ren, Zhen (2022)
A novel horn antenna is reported in this communication, which is realized by using water walls instead of traditional metallic walls. Due to its fluidity, water filling different channels can be readily controlled. Therefore, the proposed water horn antenna can operate in two states: H-plane horn state and leaky-wave state, resulting in different radiation patterns. The energy bounding effects of a water layer are initially studied for choosing the suitable thickness of the water walls. EHmn modes are excited and can propagate along the water waveguide. The E-field and H-field distributions of the EHmn modes are similar to the TE and TM modes excited inside a metallic rectangular waveguide. Propagation constants of the EHmn modes have been extracted from simulation results, and it is found that a leaky wave can be excited. Measured results show that the proposed water horn antenna has an impedance bandwidth (|S11| <−10 dB) from 2.5 to 5.2 GHz (70.1% fractional bandwidth) for the H-plane horn state and from 2.6 to 5.7 GHz (74.7% fractional bandwidth) for the leaky-wave state. The proposed antenna achieves a maximum gain of 11.8 dBi for the H-plane horn and 7.7 dBi for leaky-wave state. The proposed water horn antenna has the advantages of reconfigurability and transparency, which may be potentially useful in many wireless communication applications.